Right to information (RTI) legislation: the role of infomediaries in enhancing citizens' access to information. Issue 1 (2nd January 2016) - Fattah, Kazi Nazrul
ABSTRACT: Merely creating a legal space by enacting right to information (RTI) legislation is often not enough to ensure citizens', especially women's, access to information. Based on a pilot intervention on RTI implementation in Bangladesh, this article explores whether the introduction of information intermediaries, or "infomediaries", enhances rural citizens' access to information through using the RTI Act. It was found that due to the assisted access provided by infomediaries, the number of RTI Act users increased significantly in the intervention areas compared to the national average, with five times more women than men being able to use the Act.